Development of bending tests for near shear mode interfacial toughness measurement of EB-PVD thermal barrier coatings. (15th February 2017) - Vaunois, Jean-Roch; Poulain, Martine; Kanouté, Pascale; Chaboche, Jean-Louis
Highlights: Method for the measurement of interfacial toughness in TBCs at large mode mixities. An energetic equivalence to consistently determine the interfacial mode mixity angle. Complete characterization of interfacial toughness in a TBC after various aging histories. Abstract: Mechanisms leading to degradation of the mechanical adhesion of thermal barrier coatings (TBCs) used in aircraft turbines are numerous and complex. Direct measurement of interface toughness as a function of thermal cycling exposure must be a component of any practical approach to lifetime assessment based on a spallation criterion. This paper outlines several adhesion tests, where the multilayered system undergoes different mechanical loading. The notion of mode mixity angle is reminded and a method for its determination is described. Of course, this method to compute the mode mixity angle can be useful for any thin film delamination problem. Some results on the TBC adhesion energy are presented, relating to both the temperature and the time-of-aging for relevant mode mixity consistent with the spallation configurations observed from feedback on ex-service blades. The effect of the residual stresses induced during thermal cycling is considered here, in order to derive the intrinsic critical energy release rate. The whole set of data enables a description to be made of the intrinsic interfacial toughness decreasing under both thermal aging and mechanical loading. Finally, an energetic approach is used to compare this intrinsic interfacial toughness to the elastic stored energy during thermal cycling, in order to assess the lifetime corresponding to spontaneous spallation.